2018
DOI: 10.5194/angeo-36-1027-2018
|View full text |Cite
|
Sign up to set email alerts
|

A possible source mechanism for magnetotail current sheet flapping

Abstract: Abstract. The origin of the flapping motions of the current sheet in the Earth's magnetotail is one of the most interesting questions of magnetospheric dynamics yet to be solved. We have used a polar plane simulation from the global hybrid-Vlasov model Vlasiator to study the characteristics and source of current sheet flapping in the center of the magnetotail. The characteristics of the simulated signatures agree with observations reported in the literature. The flapping is initiated by a hemispherical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…This simulation run was previously used in several studies focusing on various phenomena and regions in the near-Earth space, such as dayside magnetopause reconnection (Hoilijoki et al, 2017), ion acceleration in the magnetosheath (Jarvinen et al, 2018), magnetotail reconnection (Palmroth et al, 2017;Juusola et al, 2018a), and magnetotail current sheet flapping (Juusola et al, 2018b). In each of these studies, the presented results showed good correspondence with earlier findings.…”
supporting
confidence: 78%
“…This simulation run was previously used in several studies focusing on various phenomena and regions in the near-Earth space, such as dayside magnetopause reconnection (Hoilijoki et al, 2017), ion acceleration in the magnetosheath (Jarvinen et al, 2018), magnetotail reconnection (Palmroth et al, 2017;Juusola et al, 2018a), and magnetotail current sheet flapping (Juusola et al, 2018b). In each of these studies, the presented results showed good correspondence with earlier findings.…”
supporting
confidence: 78%
“…Recently, simulation results show that subsolar magnetopause reconnections can create hemispherically asymmetric magnetopause perturbations, which initiate flapping motions (Juusola et al, 2018). Magnetosonic waves are expected to be launched within the local tail, which can be regarded as a cavity, and their travel time within the cavity determines the period of the flapping (Juusola et al, 2018). As a comparison, the periods of the flapping in Figure 3 are almost the same with the variations of V Z, SW , indicating that another mechanism could contribute to the generation of this flapping.…”
Section: Discussionmentioning
confidence: 99%
“…Flapping motions can be generated by external sources (Shen et al, 2008) as well as internal sources (Malova et al, 2007;Wei et al, 2015). Recently, simulation results show that subsolar magnetopause reconnections can create hemispherically asymmetric magnetopause perturbations, which initiate flapping motions (Juusola et al, 2018). Magnetosonic waves are expected to be launched within the local tail, which can be regarded as a cavity, and their travel time within the cavity determines the period of the flapping (Juusola et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observational studies at Earth (Forsyth et al, 2009;Sun et al, 2014) demonstrated that the magnetic double-gradient instability model best describes the observational data. Other observational (Forsyth et al, 2009;Shen et al, 2008) and numerical (Juusola et al, 2018;Sergeev et al, 2008) studies had also proposed solar wind variations as an external source for the excitation of flapping waves within Earth's magnetotail.…”
Section: Introductionmentioning
confidence: 99%